2016
DOI: 10.46743/2160-3715/2016.2505
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Readiness for Clinical Practice: Students’ Perspectives of their Veterinary Curriculum

Abstract: Studies describing the effectiveness of a veterinary curriculum from the student perspective are currently sparse. The overall purpose of this investigation was to describe students’ perceived preparedness for clinical practice. Three focus group meetings with fourth year veterinary students were conducted. Data were open-coded and categorized to identify themes. Four main themes emerged: Challenging communications, Un/appreciating curricular experiences, Documenting demands impede case involvement, and Hunger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The veterinarian clinicians also indicated that they should be patient and give clients time to digest bad news about their animals before prompting them to make decisions. However, they should show empathy in an honest manner that does not obscure the expectations of and understanding for the client, see quote 16.…”
Section: Interpersonal Communication (Developing Empathy and Building Relationships)mentioning
confidence: 99%
See 1 more Smart Citation
“…The veterinarian clinicians also indicated that they should be patient and give clients time to digest bad news about their animals before prompting them to make decisions. However, they should show empathy in an honest manner that does not obscure the expectations of and understanding for the client, see quote 16.…”
Section: Interpersonal Communication (Developing Empathy and Building Relationships)mentioning
confidence: 99%
“…[8][9][10][11][12][13] Despite the general recognition of the crucial nature of veterinarians' communication training, studies have still indicated that some students and practitioners require more preparation. 10,[14][15][16] Teaching communication skills is fundamental in veterinary clinical training; most veterinary practitioners believed that communication skills are important, and some would consider communication to be a clinical skill in part due to the significant impact of veterinarian's communication skills on the enhancement of accuracy and efficiency in veterinary practices. 2,5,6,17 Communication strategies and interpersonal skills are significant in building rapport with clients and achieving satisfying practitioner-client relationships.…”
Section: Introductionmentioning
confidence: 99%